2009
DOI: 10.1159/000243079
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of High Anxiety Level on Cellular and Humoral Immunity in Mice

Abstract: Background/Aims: In the present study, we aimed to examine whether a high anxiety level affects various parameters of immunity in mice. Methods: We used the behavioral light/dark choice test to evaluate whether high anxiety has an impact on various parameters of cellular (granulocytes, monocytes, total lymphocytes, TCD4+, TCD8+ and NK numbers) and humoral (IgA, E and G concentrations) immunity. Secondly, we investigated whether the cellular and humoral immune systems of mice with contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 92 publications
1
21
0
Order By: Relevance
“…However, a correlation between intracellular ROS levels and high anxiety has been found in mice (Bouayed et al, 2009;Hovatta et al, 2005;Kromer et al, 2005;Rammal et al, 2008a;Rammal et al, 2008b). It has been hypothesized that oxidative stress might be responsible for an immune perturbation in highly anxious mice (Rammal et al, 2010). Also, psychological stress induces oxidative stress by reducing antioxidant defenses (Zafir and Banu, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, a correlation between intracellular ROS levels and high anxiety has been found in mice (Bouayed et al, 2009;Hovatta et al, 2005;Kromer et al, 2005;Rammal et al, 2008a;Rammal et al, 2008b). It has been hypothesized that oxidative stress might be responsible for an immune perturbation in highly anxious mice (Rammal et al, 2010). Also, psychological stress induces oxidative stress by reducing antioxidant defenses (Zafir and Banu, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Hawley et al (2006) showed that stress caused by high social competition in birds involves a lower production of anti-sheep erythrocytes. Rammal et al (2010) found that anxious mice produced fewer IgA and IgE antibodies than their nonanxious counterparts, and when both groups were subjected to restraint stress, it appears that all studied antibodies (IgA, IgE and IgG) were suppressed in both groups. On the other hand, Guéguinou et al (2011) analyzed the natural antibodies of mice subjected to a rotational velocity model (2 and 3 G-force) for 21 days and found an increase in IgG levels of animals subjected to 2Gs.…”
Section: Discussionmentioning
confidence: 89%
“…Rammal et al. have shown that high levels of anxiety and restraint stress can impair cellular and humoral immunity in mice by decreasing T lymphocyte numbers and immunoglobulin concentrations 6 . In human studies, psychosocial stress appeared to reduce immunological control over latent herpes virus, 13 and particularly VZV as demonstrated by Irwin et al.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, suppressed immune response has frequently been reported in association with psychiatric disorders. Animal models have shown that cellular and hormonal immune systems are inhibited in highly anxious mice, leading to impaired immune response 6 . Research has also suggested that psychological stress, anxiety and depression exert an adverse effect on immune function and increase susceptibility to infection 7–10 .…”
Section: Introductionmentioning
confidence: 99%